Intra-Abdominal Abscess Drainage: Interval to Surgery - Park, Jong; Charles, Hearns W. (Seminars in Interventional Radiology, 2012)
Placement of percutaneous drainage catheters has become first-line therapy in the treatment of patients with intra-abdominal abscesses. Catheters can be used to avoid surgical intervention or to improve surgical outcomes. This article discusses the current evidence describing the optimal interval between percutaneous drainage procedures and surgery, focusing on patients with Crohn's disease, appendicitis, and diverticulitis.
Keywords: interventional radiology; abscess; percutaneous drainage; abdominal; appendicitis; Crohn's disease; diverticulitis